2022
DOI: 10.3390/foods11101460
|View full text |Cite
|
Sign up to set email alerts
|

Sprouts Use as Functional Foods. Optimization of Germination of Wheat (Triticum aestivum L.), Alfalfa (Medicago sativa L.), and Radish (Raphanus sativus L.) Seeds Based on Their Nutritional Content Evolution

Abstract: Wheat, alfalfa, and radish sprouts are well-renowned for their high nutritional content. However, their optimal imbibition and germination durations are rarely considered in the literature. In this study, reduced imbibition times of 3 h, 10 h, and 4 h were demonstrated for the wheat, alfalfa, and radish seeds, respectively. The evolution of their crude fat, proteins, polyphenols, antioxidant activity, and vitamins were investigated over 7 days of germination. The crude fat and protein loads of these sprouts sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…Still, it may differ in effect from one seed to another and between one environment and another, and the optimal soaking time in his research was only 4 hours to germinate by 88%, which may indicate that they do not need soaking in general, but instead only washing and moisturizing the seeds, since the process of producing plants depends on the presence of water permanently, and the effect of the storage period is clearly shown in increasing the proportion of nutritional components. This result is consistent with the finding of [10] that the optimal storage period for the radish sprouts to give the best nutritional components is 4, 6, and 7 days.…”
Section: Raw Protein Percentagesupporting
confidence: 92%
See 2 more Smart Citations
“…Still, it may differ in effect from one seed to another and between one environment and another, and the optimal soaking time in his research was only 4 hours to germinate by 88%, which may indicate that they do not need soaking in general, but instead only washing and moisturizing the seeds, since the process of producing plants depends on the presence of water permanently, and the effect of the storage period is clearly shown in increasing the proportion of nutritional components. This result is consistent with the finding of [10] that the optimal storage period for the radish sprouts to give the best nutritional components is 4, 6, and 7 days.…”
Section: Raw Protein Percentagesupporting
confidence: 92%
“…The treatment a2b1c3 (red radish with soaking seeds with the third storage period) recorded the highest value (16.38%), differing significantly compared to the lowest value (11.91%) obtained by treatment a3b1c3. We notice that despite the soaking treatment did not affect the protein percentage significantly, it was influential in the binary and triple interaction of radish sprouts, which may be due, as reported by [10] [53], to the fact that germination can change the seed nutrient constitution. He also mentioned that radish seeds absorb water well.…”
Section: Raw Protein Percentagementioning
confidence: 61%
See 1 more Smart Citation
“…For whole lentil, the GS of FG (2.03 mg/g GAE DW) and LG (2.08 mg/g GAE DW) exhibited significantly decreased TPC compared with the NGS (3.09, 2.65 mg/g GAE DW for FG and LG, respectively), whereas the GS of LR (1.02 mg/g GAE DW) showed significantly increased TPC compared with the NGS (0.86 mg/g GAE DW). It has been shown that germination increases the TPC in sprouted seeds of several plants, including sunflower, radish, mung bean, and soybean [ 9 , 10 , 29 , 30 ]. However, germination has been reported to reduce the TPC content in lentils [ 31 ], similar to the FG and LG varieties but contrary to the LR variety ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
“…The significantly reduced ABTS radical scavenging ability of the seeds coats might be responsible for these results, as the AA of the endosperms were significantly increased ( Figure 4 B). In crops such as mung bean, soybean, radish, buckwheat, etc., the positive effects of germination on AA have been extensively reported [ 11 , 29 , 30 ]. The rise in AA during germination is likely related to the quantitative increase in antioxidants such as polyphenols.…”
Section: Resultsmentioning
confidence: 99%